Understanding pedagogy and its impact on learning - Mortimore, Peter; Sage eBooks (London : Paul Chapman, 1999)
Bringing together what is known about pedagogy in relation to different groups of learners, from under-fives to adult education, this book also looks at the key areas of special needs and IT education.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Teaching -- England; Learning -- England; Electronic books